The dialectic of public space and mass media in the 21st century - بوبكر الصديق بن شويخ (International Journal of Social Communication, 2020)
The subject of this research paper revolves around the concept of bourgeois public space, and its relationship to the mass media, which some considered an extension of it, while others described it as the means of domination and control, and a restriction of political freedoms and practices. On this basis, we tried to capture various opinions, by presenting a critical analytical view in order to stimulate discussion, and highlight the relationship that exists between the bourgeois public space and the mass media and communication in the 21st century